Pacritinib versus best available therapy for the treatment of myelofibrosis irrespective of baseline cytopenias (PERSIST-1): an international, randomised, phase 3 trial - Mesa, R; Vannucchi, A; Mead, A; Egyed, M; Szoke, A; Suvorov, A; Jakucs, J; Perkins, A; Prasad, R; Mayer, J; Demeter, J; Ganly, P; et al. (Lancet, 2017)
Background: Available therapies for myelofibrosis may exacerbate cytopenias and are not indicated for patients with severe thrombocytopenia. The JAK2/FLT3 inhibitor pacritinib induced spleen responses with limited myelosuppression in phase 1/2 trials. We aimed to assess the efficacy and safety of pacritinib vs best available therapy in patients with myelofibrosis irrespective of baseline cytopenias. Methods: In the international phase 3 PERSIST-1 trial, patients with higher-risk myelofibrosis (no exclusions for baseline anemia or thrombocytopenia) were randomized 2:1 to receive oral pacritinib 400 mg once-daily or best available therapy (BAT; excluding JAK2 inhibitors) until disease progression or unacceptable toxicity. Randomization was stratified by risk category, platelet count, and region. The primary endpoint was spleen volume reduction (SVR) ≥35% from baseline to week 24 in the intent-to-treat population as assessed by blinded, centrally reviewed magnetic resonance imaging or computed tomography. Herein, final data with a median follow-up 23·2 months are presented. This trial is registered with clinicaltrials.gov, NCT01773187. Findings: Between 8Jan2013-1Aug2014, 327 patients were randomized 2:1 to pacritinib (n=220) or BAT (n=107). At week 24, the primary endpoint of SVR ≥35% was achieved by 19·1% (n=42) vs 4·7% (n=5) of pacritinib- vs BAT-treated patients (P=0·0003). The most common grade 3/4 adverse events through week 24 were anemia (37 [16·8%]), thrombocytopenia (26 [11·8%]), and diarrhea (11 [5·0%]) with pacritinib, and anemia (16 [15·1%]), thrombocytopenia (12 [11·3%]), dyspnea (3 [2·8%]), and hypotension (3 [2·8%]) with BAT; the most common serious adverse events were anemia (10 [4·5%]), cardiac failure (5 [2·3%]), pyrexia (4 [1·8%]), and pneumonia (4 [1·8%]) with pacritinib, and anemia (5 [4·7%]), sepsis (2 [1·9%]), and dyspnea (2 [1·9%]) with BAT. Interpretation: Pacritinib therapy was well-tolerated and induced significant and sustained SVR and symptom reduction, even in patients with severe baseline cytopenias. Pacritinib could be a treatment option for patients with myelofibrosis, including those with baseline cytopenias for whom current options are particularly limited.